The missing reason to fill in the blank is "substitution."
Thus, the complete proof segment would read as follows:
- ST¯¯¯¯¯¯¯ is the midsegment of trapezoid WXYZ.
- Given SU¯¯¯¯¯¯¯∥WX¯¯¯¯¯¯¯¯¯¯ UT¯¯¯¯¯¯¯∥ZY¯¯¯¯¯¯¯.
- Definition of midsegment (trapezoid).
- SU¯¯¯¯¯¯¯ is the midsegment of △WXZ.
- UT¯¯¯¯¯¯¯ is the midsegment of △XYZ.
- Definition of midsegment (triangle).
- SU = 1/2 WX
- UT = 1/2 ZY
- Midsegment Theorem.
- ST = SU + UT
- ST = 1/2 WX + 1/2 ZY (substitution)
- ST = 1/2 (WX + ZY) (Distributive Property)
In this sequence, the step that justifies the equality ST = 1/2 WX + 1/2 ZY is due to substitution.